Kebijakan Pencegahan Korupsi Sektor Sumber Daya Alam Melalui Pendekatan Institusional dan Struktural - Kartodihardjo, Hariadi; Ariati, Niken; Abdullah, Maryati (Integritas : Jurnal Antikorupsi, 2019)
Sources of corruption that are related to the state always involving bureaucracy and institutional policies. The five-year evaluation of the implementation of the National Movement to Save Natural Resources by the Corruption Eradication Commission found its weaknesses, which became the main weaknesses. It is the result of the influence that was coming from within and outside the organization. The problem of corruption in natural resources can be identified through the development of institutional analysis (IAD). The results of this discussion indicate that corruption prevention must be agreed with politics that is adjusted with different typologies.